Strategi Lokalisasi PKL : Peranan Pemerintah Kabupaten Pamekasan Dalam Meningkatkan Perekonomian Daerah - Maulana, Wahyu; Efendi, Junaidi; Lestari Pramita Putri, Devi (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
The aim of this research is to see how the localization strategy for street vendors in Pamekasan district can improve the regional economy. This is not without reason because street vendors are a form of business in the informal sector whose existence has a significant impact on the regional economy and there are efforts from the regional government itself to encourage the informal sector by achieving quite large numbers during its term of office so that this to be sustainable and synergistic. This is certainly not easy considering that there are still many problems that need to be resolved so as to provide mutually beneficial joint solutions. This research is felt urgent to be implemented considering that there is still a lot of